Filling a gap: initial evidence for reliable and valid measures of students’ self-concept, self-efficacy, and interest in science with elementary students traditionally underrepresented in STEM - Gagnier, Kristin Michod; Holochwost, Steven J.; Ceren, Melissa; Fisher, Kelly R. (Frontiers in Education, 2024)
American students continue to perform poorly on national and international assessments of Science, Technology, Engineering, and Mathematics (STEM) competencies, and achievement gaps spanning racial/ethnic and socioeconomic lines emerge early and widen over time. Scholars and practitioners agree that expanding access to high-quality STEM education has the potential to improve students’ performance and reduce inequalities. Research has elucidated the critical role that students’ self-perceptions play in driving academic achievement, which has spurred the development of many educational programs and initiatives aimed at increasing students’ confidence, self-efficacy, and interest. However, our capacity to determine what programs and initiatives are effective and for whom is limited by our lack of psychometrically sound measures that assess science-related self-perceptions and interests of elementary students from diverse populations. To address this gap, we developed and tested measures of Science Self-Efficacy, Science Self-Concept, Interest in Science Activities, and Attitudes toward STEM careers in a sample of third-grade students (8–9 years) traditionally underrepresented in STEM careers (94% of our sample identified as either African American or Hispanic). We present initial evidence, from a preliminary pilot study, for the reliability and validity of these measures and reveal the multi-dimensional nature of students’ self-perceptions and interests in science. We discuss how such measurement tools will inform our understanding of the nature of young students’ science self-perceptions, how the utilization of such tools can inform educational practice, and highlight the critical importance of conducting measurement development research with diverse populations.